A Study on Dietary Intake Categories and Fasting Blood Glucose Serum Among Adults with Type 2 Diabetes Mellitus - isa, Farah Nuriann; Yuliani, Kartika (International Journal of Psychosocial Rehabilitation, 2020)
Lifestyle & diet management is needed in adults with T2DM. Usually, adults with T2DM had low diet compliance, their intake either lower or higher than their requirements. However, dietary intake is a main factor contribute in fasting blood glucose (FBG) level in T2DM patient. The aim of this study was to investigate the difference between dietary intake categories and FBG level in T2DM patients. This study used cross sectional design with total sample size 30 T2DM patients from three public health centres in Yogyakarta. Dietary intake was collected with multiple 24h-recall and divided into three group based on comparison with subjects’ nutrient requirements. The FBG level was assessed once at the end of study. From this study, we could see that majority of the subjects had insufficient dietary intake, except fat and sucrose. We also found that the higher level of dietary intake of the subjects, the higher levels of their FBG. FBG levels increased as the subjects consumed food more than their needs, but no significant difference among three groups statistically. This study suggested all the health center to assess diet compliance in T2DM patients periodically so they could attain normal blood glucose.